2023
DOI: 10.1039/d3cc00005b
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom catalysts for electrochemical applications

Abstract: The field of small molecule electro-activated conversion is becoming a new star in modern catalytic research toward the carbon-neutral future. The advent of single-atom catalysts (SACs) is expected to greatly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 108 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…In recent years, due to the development of nanotechnology, it is possible to fine-tune the structure of an electrocatalyst at the nanoscale to control the structure of the electrocatalyst, making it have better stability, catalytic activity, and product selectivity. Single-atom catalysts (SACs) with isolated transition metal (TM) atoms stabilized by carbon-based materials have attracted more and more attention due to their special electronic structure and platform utilization 12 and have become promising candidate materials in the nitrogen reduction reaction, 13 HER, 14–16 oxygen reduction reaction, 15,17 oxygen evolution reaction, 18,19 CO 2 RR, 20,21 and other reactions. 22 Previous studies have indicated that catalysts such as Mn, Mo, Ru, and Ti offer distinct advantages in the CO 2 RR compared to the HER, requiring lower overpotentials for the generation of intermediate products (*COOH or *OCHO).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to the development of nanotechnology, it is possible to fine-tune the structure of an electrocatalyst at the nanoscale to control the structure of the electrocatalyst, making it have better stability, catalytic activity, and product selectivity. Single-atom catalysts (SACs) with isolated transition metal (TM) atoms stabilized by carbon-based materials have attracted more and more attention due to their special electronic structure and platform utilization 12 and have become promising candidate materials in the nitrogen reduction reaction, 13 HER, 14–16 oxygen reduction reaction, 15,17 oxygen evolution reaction, 18,19 CO 2 RR, 20,21 and other reactions. 22 Previous studies have indicated that catalysts such as Mn, Mo, Ru, and Ti offer distinct advantages in the CO 2 RR compared to the HER, requiring lower overpotentials for the generation of intermediate products (*COOH or *OCHO).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they offer the additional benefit of improved cost effectiveness due to maximized atomic utilization and tunable electronic configurations. [33][34][35][36][37][38] While SACs have shown commendable performance in controlled laboratory settings and within membrane electrode assemblies (MEAs), their long-term stability under the demanding conditions of an operating PEMFCs remains a critical area of concern. [39][40][41][42] A number of issues, including metal dissolution, poisoning of the active sites and corrosion of the carbon support, present significant challenges to the durability and reliability of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Compared to solid nanoparticles, single-atoms (SAs) species as the ''Holy Grail'', owing to their super-high utilization of active atoms, non-saturated atomic coordination sites, and uniformity of active centers, stand out. 18,19 Specifically, single-atom materials are considered promising candidates for accelerating the electrochemical conversion kinetics of lithium-oxygen batteries, [20][21][22] lithium-sulfur batteries, [23][24][25] and zinc-air batteries 26,27 because the individual catalytic sites with unsaturated metal coordination are believed to facilitate electron transfer and redox reactions in the batteries, thus improving their electrochemical performance. [28][29][30][31][32][33][34] In this case, we speculate whether a single-atom catalyst can effectively improve the electrochemical performance of lithiumrich oxygen batteries.…”
Section: Introductionmentioning
confidence: 99%